Reliability and Safety of Structural Elements in the Gigacycle Region of Loading - Novy, Frantisek; Ulewicz, Robert; Bokuvka, Otakar; Trsko, Libor; Lago, Jan (Communications - Scientific Letters of the University of Zilina, 2016)
The authors of this paper, based on their own results, discuss fatigue properties of low-alloyed fine-grained steel STRENX 700MC obtained in the ultra-high-cycle region (gigacycle fatigue) with regard to the reliability and safety of structural elements. According to obtained data it is obvious that fatigue strength continuously decreases with increasing number of cycles to failure (in a range from N = 10(7) to N = 10(10) cycles). Fatigue limit σc determined usually at N = 2 * 10(6) / 10(7) cycles does not meet the requirements of reliability and safety of structural elements. Design of structural elements which will be working in the ultra-high-cycle fatigue region requires complete information about fatigue behavior of used structural materials.
Keywords: reliability; safety; steel STRENX 700MC; structural elements; gigacycle fatigue